Production of indole-3-acetic acid by Thai native orchid-associated fungi - Chutima R. (2014)
Thirteen endophytic fungi were isolated from roots of three orchid species, Spathoglottis affinis, Paphiopedelum bellatulum and Phaius tankervilleae. Of these, three fungal isolates produced high levels of indole-3-acetic acid (IAA) in culture medium supplemented with 2 mg/ml of L-tryptophan, and were selected for further analysis. Morphological characteristics and a phylogenetic analysis based on an alignment of internal transcribed spacer regions of nuclear rDNA indicated that the fungal isolates CMU-SLP 007 and CMU-NUT 013 belonged to family Tulasnellaceae, genus Tulasnella (the anamorphic genus Epulorhiza) and the fungal isolate CMU-AU 006 belonged to Colletotrichum gloeosporioides. These three fungal isolates produced maximum levels of IAA when grown in a culture medium supplemented with 4 mg/ml of L-tryptophan (C. gloeosporioides CMU-AU 006, 243.56 μg/ml and Tulasnella sp. CMU-SLP 007, 155.63 μg/ml) and 6 mg/ml of L-tryptophan (Tulasnella sp. CMU-NUT 013, 104.03 μg/ml). Thin layer chromatography revealed that all fungal IAA presented the same R f value as the standard IAA. The biological activity of fungal IAA showed that it increased the length of stem forming roots and the number of roots of kidney bean (Phaseolus vulgaris), promoted seed germination, the length of roots and root to shoot ratio of corn (Zea mays) and increased the elongation of rice (Oryza sativa) coleoptiles when compared with all controls (water and culture medium treatments). In addition, the results of all biological activities using fungal IAA indicated that the quality of fungal IAA were similar to standard IAA. © 2012 Springer Science+Business Media B.V.